Peran Pendidikan Dalam Membangun Karakter Bangsa Indonesia - Amini, Amini; Putra, Hermansyah; Putri Siregar, Chynda Zumalia; Fatahillah, Muhammad; Zulviannas, Rizti; Hasibuan, Maisyaroh (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Education as a place for students to gain knowledge with the teaching given by the teacher in order to build the personality of students so that they have good character and noble character. The teacher as a teaching provider does not only provide lessons in the classroom, but also as a character building for students to be able to have a noble attitude in the surrounding environment. The method used in this research is qualitative method. The purpose of this study is to find out and examine how the role of education plays a role in shaping student character. The results of this study indicate that the role of education is very good. This can be seen from students who have good personalities. However, there are a number of things that need to be improved, such as the activeness of the teacher in giving moral messages to students in learning. keywords: role, education, character